Functional Materials 2019
DOI: 10.5772/intechopen.84228
|View full text |Cite
|
Sign up to set email alerts
|

Janus Nanosheets Derived from K4Nb6O17·3H2O via Regioselective Interlayer Surface Modification

Abstract: Inorganic Janus nanosheets were successfully prepared using the difference in reactivity between interlayers I and II of layered hexaniobate K 4 Nb6O 17 ·3H 2 O. Janus nanosheets exhibit the highest anisotropy among Janus compounds due to their morphology. It is therefore important to prepare Janus nanosheets with stable shapes in various solvents, robust chemical bonds between nanosheets and fuctional groups and high versatility due to surface functional groups. K 4 Nb 6 O 17 ·3H 2 O, which possesses two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…28 It is therefore concluded that Nb–O–P bonds were additionally formed between the PA moiety and niobate layer. Based on our previous study using the same set of alkylammonium ions for preparing intermediates, 25 it can be concluded that PPA and PA moieties were mobilized in interlayers I and II by two-step surface modification. Based on our previous study on interlayer surface modification of K 4 Nb 6 O 17 ·3H 2 O by PPA, both PPA and moieties should be present in PhP(O)(OH)O–Nb and/or (HO) 2 P(O) O–Nb monodentate environments.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…28 It is therefore concluded that Nb–O–P bonds were additionally formed between the PA moiety and niobate layer. Based on our previous study using the same set of alkylammonium ions for preparing intermediates, 25 it can be concluded that PPA and PA moieties were mobilized in interlayers I and II by two-step surface modification. Based on our previous study on interlayer surface modification of K 4 Nb 6 O 17 ·3H 2 O by PPA, both PPA and moieties should be present in PhP(O)(OH)O–Nb and/or (HO) 2 P(O) O–Nb monodentate environments.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, weak signals assignable to n -dodecyl chains in C 12 N + were observed at 16–41 ppm, a result indicating the presence of C 12 N + in PPA_PA_NbO. 25…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations